The Efficiency of The Training Programme in Test-Takers Scoring Who Participate in Preparation TOEFL Test Course Held in Staff Development Centre (Journal of the College of Basic Education, 2023)
This paper aims at measuring the effectiveness of the ( Preparation for TOEFL Test Training programme ) conducted by Staff Development Centre on the participants' achievement in the post – test at the end of the programme . Two groups have been selected for this purpose (experimental and control group ) containing (15) participants each . The experimental group was taught by using computer assisted instruction in special lecture room provided with LCD screen ( clear sound , clear pictures ) with special TOEFL CDs and books from local market and other designed by the staff of the center to reinforce the learning process . The second group was taught using the traditional method ( cassettes , board ) . The programme for each group lasted ( 4) weeks . The participants in both groups subjected to a post–test which is the same for both using the statistical analysis T-test . The results showed the achievement of experimental group in post–test was much better than the other group . The paper concludes that the teaching methods applications and using modern techniques and various audio – visual aids can highly improve the efficiency of the programme and it also recommends that CDs and computer-assisted language learning should be incorporated into the regular classes, rather than scheduling them separately. The paper came out with some recommendations in this respect .